Feeding strategies of tropical and subtropical calanoid copepods throughout the eastern Atlantic Ocean – Latitudinal and bathymetric aspects. (November 2015) - Bode, Maya; Hagen, Wilhelm; Schukat, Anna; Teuber, Lena; Fonseca-Batista, Debany; Dehairs, Frank; Auel, Holger
Highlights: Trophic interactions of copepods were analyzed in the (sub)tropical Atlantic Ocean. FA and SI revealed inter- and intra-specific differences in feeding strategies. Herbivorous, omnivorous and carnivorous copepods showed typical carnivory indices. Epi- to mesopelagic copepods reflected spatial differences in baseline δ 15 N of POM. Deep-living copepods did not show this regional trend and had higher δ 15 N. Abstract: The majority of global ocean production and total export production is attributed to oligotrophic oceanic regions due to their vast regional expanse. However, energy transfers, food-web structures and trophic relationships in these areas remain largely unknown. Regional and vertical inter- and intra-specific differences in trophic interactions and dietary preferences of calanoid copepods were investigated in four different regions in the open eastern Atlantic Ocean (38°N to 21°S) in October/November 2012 using a combination of fatty acid (FA) and stable isotope (SI) analyses. Mean carnivory indices (CI) based on FA trophic markers generally agreed with trophic positions (TP) derived from δ 15 N analysis. Most copepods were classified as omnivorous (CI ∼0.5, TP 1.8 to ∼2.5) or carnivorous (CI ⩾ 0.7, TP ⩾ 2.9). Herbivorous copepods showed typical CIs of ⩽0.3. Geographical differences in δ 15 N values of epi- (200–0 m) to mesopelagic (1000–200 m) copepods reflected corresponding spatial differences in baseline δ 15 N of particulate organic matter from the upper 100 m. In contrast, species restricted to lower meso- and bathypelagic (2000–1000 m) layers did not show this regional trend. FA compositions were species-specific without distinct intra-specific vertical or spatial variations. Differences were only observed in the southernmost region influenced by the highly productive Benguela Current. Apparently, food availability and dietary composition were widely homogeneous throughout the mesotrophic oceanic regions of the tropical and subtropical Atlantic. Four major species clusters were identified by principal component analysis based on FA compositions. Vertically migrating species clustered with epi- to mesopelagic, non-migrating species, of which only Neocalanus gracilis was moderately enriched in lipids with 16% of dry mass (DM) and stored wax esters (WE) with 37% of total lipid (TL). All other species of this cluster had low lipid contents (<10% DM) without WE. Of these, the tropical epipelagic Undinula vulgaris showed highest portions of bacterial markers. Rhincalanus cornutus, R. nasutus and Calanoides carinatus formed three separate clusters with species-specific lipid profiles, high lipid contents (⩾41% DM), mainly accumulated as WE (⩾79% TL). C. carinatus and R. nasutus were primarily herbivorous with almost no bacterial input. Despite deviating feeding strategies, R. nasutus clustered with deep-dwelling, carnivorous species, which had high amounts of lipids (⩾37% DM) and WE (⩾54% TL). Tropical and subtropical calanoid copepods exhibited a wide variety of life strategies, characterized by specialized feeding. This allows them, together with vertical habitat partitioning, to maintain high abundance and diversity in tropical oligotrophic open oceans, where they play an essential role in the energy flux and carbon cycling.